Outcome after neoadjuvant chemotherapy in estrogen receptor-positive and progesterone receptor-negative breast cancer patients: a pooled analysis of individual patient data from ten prospectively randomized controlled neoadjuvant trials - Mackelenbergh, Marion Tina van; Denkert, Carsten; Nekljudova, Valentina; Karn, Thomas; Schem, Christian; Marmé, Frederik; Stickeler, Elmar; Jackisch, Christian; Hanusch, Claus; Huober, Jens; Fasching, Peter A.; Blohmer, Jens-Uwe; et al. (Breast cancer research and treatment, 2018)
The estrogen receptor (ER) is involved in control of progesterone receptor (PgR) expression and lack of PgR may be also a surrogate of altered growth factor signaling. The aim of this study was therefore to investigate PgR expression as predictive factor for response to neoadjuvant therapy and long-term outcome.
Gesehen am 19.03.2020
Published online: 5 September 2017